“Du kommer aldrig bli en sån karl” - En reparativ läsning av maskulinitetsuttryck i Bränn alla mina brev och Jävla Karlar - Sande,Matilda (2025)
This thesis analyzes the novels Bränn alla mina brev and Jävla Karlar with focus on expressions of masculinities. The method is reparative reading which entails reading from a position of hope. The theoretical framework is primarily based on Connell’s masculinity theories, which are the hegemonic, complicit, subordinated, and marginalized masculinity. Complementary are Anderson’s theory of inclusive masculinity and Ekenstam and Lorentzen’s theory on what’s considered manly and unmanly. The research questions are which masculinities are depicted in the material, and which masculinities are described as desirable or not. In the analysis the findings are presented which are hegemonic masculinity, inclusive masculinity, the fear of domination by others, jealousy, dichotomy of manly–unmanly, female masculinity and parenthood. The main masculinities that are depicted are hegemonic and inclusive masculinity. Some characters express a strong hegemonic masculinity, in regard to their legitimization of mens’ domination over women. Other characters move between an inclusive and a hegemonic masculinity, however primarily leaning to the inclusive. What is seen as desirable is dependent on perspective, if seen from an individual character or societal sanctions. Lastly, I discuss the central theme of fear of domination and its consequences as well as care as a tool for transforming masculinities.
Keywords: asculinites; feminist literature studies; reparative reading; Bränn alla mina brev; Jävla Karlar; Raewyn Connell. Nyckelord: maskuliniteter; genusvetenskapliga litteraturstudier; reparativ läsning; Raewyn Connell.